2005
DOI: 10.1177/0891243204273498
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Label? The Relationship between Feminist Self-Identification and “Feminist” Attitudes among U.S. Women and Men

Abstract: Although scholars and media critics have suspected a disconnect between feminist self-identification and attitudes among the U.S. public, little is known empirically about this relationship. This article examines the relationships between feminist self-identification, sociodemographics, political orientation, and a range of gender-related attitudes using data from the 1996 General Society Survey. Results suggest that feminists are most likely to be highly educated, urban women who self-identify as liberals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
100
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 34 publications
7
100
0
3
Order By: Relevance
“…In addition, increased educational attainment is generally associated with more liberal views (McCabe 2005;Thornton and Freedman 1979), higher feminist consciousness (Reingold and Foust 1998), less traditional gender role attitudes (Marks et al 2009), and less likelihood to ascribe to traditional family values (Blanchard-Fields et al 2001;Willits and Funk 1989). However, some researchers (e.g., McCabe 2005;Schnittker et al 2003) have found this relationship only with extreme differences in the education levels.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, increased educational attainment is generally associated with more liberal views (McCabe 2005;Thornton and Freedman 1979), higher feminist consciousness (Reingold and Foust 1998), less traditional gender role attitudes (Marks et al 2009), and less likelihood to ascribe to traditional family values (Blanchard-Fields et al 2001;Willits and Funk 1989). However, some researchers (e.g., McCabe 2005;Schnittker et al 2003) have found this relationship only with extreme differences in the education levels.…”
Section: Introductionmentioning
confidence: 90%
“…Religion and politics have also been found to be related to attitudes about women's roles (Bryant 2003). Although group identification, rather than specific political affiliation, may most impact views on feminism (Rhodebeck 1996), liberal political orientation are more likely to identify as feminist (McCabe 2005;Peltola et al 2004). …”
Section: Introductionmentioning
confidence: 94%
“…First, single-item feminist ascription scales do not capture the complexity of feminist beliefs, and being a 'feminist' may mean different things to different people (McCabe, 2005;Swami & Tovée, 2006). This is also important because different aspects of feminist beliefs may be related to body image in different ways (Myers & Crowther, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Those supportive of pro-choice policies also employ the language of human rights but in the other direction. They believe women, at least at certain stages of gestation and in certain circumstances, have the right to decide to terminate their pregnancy (McCabe, 2005;Wilcox & Norrander, 2002;Adams, 1997;Sapiro & Shames, 2009;Luker, 1984). Note that neither side employs personal attitudes toward sex in defense of their own positions, though they may suspect it influences their opponents.…”
mentioning
confidence: 99%